STUDENT FILM FESTIVAL AND OTHER INNOVATIVE MEANS OF LEGAL TRAINING AND EDUCATION OF YOUNG PEOPLE - Yuriy P. Garmaev; Lidia P. Chumakova (Высшее образование в России, 2016)
In 2014 the First International Student Film Festival took place in Novosibirsk Law Institute (branch) of the National Research Tomsk State University. The festival organizersare going to hold it every year and offer to consider the project as an innovative teaching tool for law students, as well as an effective form of legal education and legal training for the general population - according to the fundamentals of the state policy in the sphere of legal literacy and legal awareness of citizens of the Russian Federation.The authors formulate here a proposal for the further development of legal science in the paradigm of creating multimedia diversified applicative solutions: training films, short manuals and booklets, manuals and programs outlined in an accessible, concise manner. This will make an important step towards the convergence of legal science and practice, the modernization of legal sciences, and most importantly - to improve the effectiveness of law enforcement, to an increase in legal culture and consciousness of the population.